Implementing a management information system for enhanced data management and institutional efficiency: a case study of the University of Pretoria. Part B - Lourens, A.; Mouton, H.J. (CUT, 2017)
The integration of university performance data with the strategic goals of a university to enhance institutional efficiency is a complex process. This article aims to illustrate the importance of the alignment of performance data with decision-support needs linked to the strategic goals of a university by means of a case study from the University of Pretoria (UP). The enhancement of the capability for monitoring and evaluating faculty indicators and departmental performance against the strategic goals of the university is illustrated through the implementation of a new management information system (known as HEDA). The focus of the article is to demonstrate the importance of integration and monitoring of the university's strategic plan for improvement in institutional efficiency. The alignment of UP's operational indicators with its Annual Performance Plan submissions required by the Department of Higher Education and Training is also outlined. The practical use and process followed for the adoption of the management information software at the university is discussed as well as the lessons learnt so far, in an attempt to monitor and integrate institutional planning at all levels
Keywords: Data management; Decision-support; Institutional effectiveness; Management information and strategic planning